1996
DOI: 10.1071/ea9960485
|View full text |Cite
|
Sign up to set email alerts
|

Seedling and adult plant evaluation of race variability in Leptosphaeria maculans on Brassica species in Australia

Abstract: Seedling and adult plant studies were used to identify the race structure of Leptosphaeria maculans (the cause of blackleg) on oilseed Brassica species in Australia. Host-pathogen interactions using a set of 12 differential host lines identified 14 seedling relationship, however, between seedling and adult plant reactions to individual isolates, indicating that seedling and adult plant resistance are under different genetic control. While non-specific adult plant resistance was observed in the B. napus line Je… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 0 publications
5
20
2
Order By: Relevance
“…Although Australian isolates of L. maculans are generally more virulent than those in Europe or Canada (Balesdent et al 2005), there was significant variability in the severity of root rot caused by different isolates. This finding is consistent with other studies that have shown variability in the pathogenicity of Australian L. maculans isolates on leaves at the seedling stage (Ballinger and Salisbury 1996) and on stems at the adult plant stage (Pang and Halloran 1995;Ballinger and Salisbury 1996).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Although Australian isolates of L. maculans are generally more virulent than those in Europe or Canada (Balesdent et al 2005), there was significant variability in the severity of root rot caused by different isolates. This finding is consistent with other studies that have shown variability in the pathogenicity of Australian L. maculans isolates on leaves at the seedling stage (Ballinger and Salisbury 1996) and on stems at the adult plant stage (Pang and Halloran 1995;Ballinger and Salisbury 1996).…”
Section: Discussionsupporting
confidence: 94%
“…Sapphire (RR 7.5) and B. juncea line Zem 1 (Marcroft et al 2002). Brassica juncea was used as this species is more resistant to L. maculans than B. napus (Ballinger and Salisbury 1996;Purwantara et al 1998;Marcroft et al 2002). Plants were grown in a glasshouse (20/15°C±2°C day/night) and were inoculated 5 weeks after sowing when they were at the four-leaf growth stage.…”
Section: Assessment Of Root Rot In Fumigated Field Plotsmentioning
confidence: 99%
“…For many pathosystems, such as Leptosphaeria maculans--B. napus, different components of resistance are thought to operate in seedlings and in older plants (Ballinger and Salisbury 1996). This may also be true for P. brassicae--B. napus, although it is possible that the large effect of environmental factors on the incidence of light leaf spot in crops contributes to the poor correlation.…”
Section: Measurement Of B Napus Resistance To P Brassicaementioning
confidence: 98%
“…Leptosphaeria maculans is the more aggressive of the two species and is capable of causing significant yield loss due to stem canker (Howlett, 2004;Fitt et al, 2006). Some isolates of L. maculans have been shown to cause stem cankers on B. juncea (Ballinger & Salisbury, 1996). Leptosphaeria biglobosa, although previously found on the stubble of both B. napus and B. juncea (Van de Wouw et al, 2008;Vincenot et al, 2008) has not been reported to cause stem canker in either species.…”
Section: Introductionmentioning
confidence: 95%